(untitled) (قضايا سياسية, 2023)
The study of the formation of Iraqi governments after 2003 is not easy، due to the repercussions of formation on the structure of the state and official The study of the formation of Iraqi governments after 2003 is not easy، due to the repercussions of formation on the structure of the state and official institutions and their dedication to the principle of sectarian and ethnic quotas and its great impact on the nature and performance of the Iraqi government The crisis of the formation of governments is the beginning of the work of the Transitional Governing Council and continued up to the October 2021 parliamentary elections due to the competitive nature of the relationship between the political parties. Those parties tend to dictate their demands instead of negotiating a common ground, in a way that renders any negotiation futile. In addition، the study looks into the repercussions of the delay in forming the government on government performance, its effect on Iraqi national security and the possibility of allowing external actors to interfere in Iraqi internal affairs. Further, this study aims to explain the extent of benefiting from ethnic and national diversity in resolving contentious issues to formulate a comprehensive national identity that is reflected positively in the government's performance. institutions and their dedication to the principle of sectarian and ethnic quotas and its great impact on the nature and performance of the Iraqi government The crisis of the formation of governments is the beginning of the work of the Transitional Governing Council and continued up to the October 2021 parliamentary elections due to the competitive nature of the relationship between the political parties. Those parties tend to dictate their demands instead of negotiating a common ground, in a way that renders any negotiation futile. In addition، the study looks into the repercussions of the delay in forming the government on government performance, its effect on Iraqi national security and the possibility of allowing external actors to interfere in Iraqi internal affairs. Further, this study aims to explain the extent of benefiting from ethnic and national diversity in resolving contentious issues to formulate a comprehensive national identity that is reflected positively in the government's performance.